ANALISIS PEMBELAJARAN PJOK BERBASIS MEDIA INTERAKTIF; TINJAUAN PADA MATERI KESELAMATAN OLAHRAGA AIR SISWA SD NEGERI LOANO KABUPATEN PURWOREJO - Pratiwi, Arista Sulistya; Saryanto; Zakariyah, Yogi Aldias (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Physical Education, Sports, and Health (PJOK) learning in elementary schools is not only oriented toward physical activity but also toward developing students’ knowledge, attitudes, and safety awareness. One important topic is water sports safety, which requires students to understand risks, preventive behavior, and emergency responses in aquatic environments. This study aimed to analyze the implementation of interactive learning media in PJOK learning on water sports safety material for sixth-grade students at SD Negeri Loano, Purworejo Regency. The study focused on four aspects: implementation of interactive media, students’ level of understanding, contribution to safety literacy, and obstacles encountered during learning. This research employed a qualitative method with a descriptive approach. Data were collected through observation, interviews, tests, and documentation, then analyzed using data reduction, data display, and conclusion. The results showed that interactive media in the form of educational videos and digital quizzes improved classroom participation and learning outcomes. The average score increased from 68.4 before implementation to 84.7 after implementation. Safety literacy also improved from 58% to 86%. Several challenges remained, including limited facilities, unstable internet access, limited learning time, and differences in student learning pace. In conclusion, interactive media proved effective as an innovative PJOK learning strategy especially for materials requiring visualization and contextual understanding such as water sports safety